The Effect of Discovery Learning in Improving SMAN 2 Tambang First-Year Students' Reading Comprehension at Recount Text - Jivi, Kevin Firdauzi; Erni, Erni; Harfal, Zaldi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The research aims to enhance reading comprehension and text analysis skills through the Discovery Learning method. A quantitative approach was used, with data collected numerically and analyzed using SPSS. A quasi-experimental design was implemented over six sessions (one month and two weeks), involving experimental and control groups of Class X students. Both groups took pre-tests and post-tests to assess their performance before and after the treatment. The experimental group received Discovery Learning in recount texts. The results showed an improvement in the scores of the experimental group. Pre-test scores ranged from 52.8 to 95.7 with an average of 72.17, while post-test scores ranged from 72.6 to 95.7 with an average of 82.17. The control group's pre-test scores ranged from 29.7 to 100 with an average of 63.16, and post-test scores ranged from 52.8 to 100 with an average of 70.87. The average post-test score of the experimental group was higher than that of the control group (82.17 vs 70.87). These findings indicate that Discovery Learning significantly improves English reading comprehension in recount texts at SMAN 2 Tambang.